Mitochondria-Targeted Drug Delivery in Cardiovascular Disease: A Long Road to Nano-Cardio Medicine - Francesca Forini; Paola Canale; Giuseppina Nicolini; Giorgio Iervasi (MDPI AG, 2020)
Cardiovascular disease (CVD) represents a major threat for human health. The available preventive and treatment interventions are insufficient to revert the underlying pathological processes, which underscores the urgency of alternative approaches. Mitochondria dysfunction plays a key role in the etiopathogenesis of CVD and is regarded as an intriguing target for the development of innovative therapies. Oxidative stress, mitochondrial permeability transition pore opening, and excessive fission are major noxious pathways amenable to drug therapy. Thanks to the advancements of nanotechnology research, several mitochondria-targeted drug delivery systems (DDS) have been optimized with improved pharmacokinetic and biocompatibility, and lower toxicity and antigenicity for application in the cardiovascular field. This review summarizes the recent progress and remaining obstacles in targeting mitochondria as a novel therapeutic option for CVD. The advantages of nanoparticle delivery over un-targeted strategies are also discussed.